(untitled) ("Temas Sociais" Journal, 2023)
Through documentary analysis of primary and secondary sources of four Social Action Services, with timeframe from 2008 to 2014, we systematized information regarding the design of Social Action policy in Portuguese state universities. The results indicate adherence to a support model identified in a set of European countries, which influences the ability to serve. The final product is the proposition of its own paradigm, with its characteristics, potentialities and constraints.